Association between food allergy and ankylosing spondylitis: An observational study. Issue 6 (February 2019) - Niu, Qian; Wei, Wei; Huang, Zhuochun; Zhang, Junlong; Yang, Bin; Wang, Lanlan
Abstract : Abstract: Food allergies can alter the gut microbiome composition, increasing the risk of conditions such as ankylosing spondylitis (AS). To identify the association between specific allergens and AS, we investigated the differences in the serum levels of 14 food antigen-specific immunoglobulin (Ig) G between AS patients and healthy participants. The association between the levels of these antibodies and disease activity was assessed by measuring the inflammatory marker C-reactive protein (CRP). We enrolled 75 AS patients and 78 healthy controls who had undergone antigen-specific IgG tests in West China Hospital between January 2015 and October 2017, and performed enzyme-linked immunosorbent assays for specific IgG against 14 food allergens: rice, egg, mushroom, milk, pork, chicken, beef, crab, codfish, corn, soybean, tomato, shrimp, and wheat. The following tests were used to analyze differences between AS patients and healthy controls: χ 2 test for sex, and a 2-tailed Student t -test or Mann–Whitney U test based on the results of Levene test for age and IgG levels. Correlations between IgG and CRP levels were calculated using a Spearman's correlation. AS patients had significantly higher serum levels of beef-, crab-, and pork-specific IgG than did healthy participants. In addition, the serum levels of pork-specific IgG were significantly and positively correlated with CRP. These results suggest that α-Gal, the predominant natural antigen in mammalian red meat, might play a potential role in the pathogenesis of AS, and therefore, AS patients should exclude such allergenic foods, including beef, crab and pork, from their daily diet.